Teoria moral kantiana e a formação do homem moralmente bom - Daniel, Nilmar Costa (2015)
The present study discusses the union among relations based on the philosophical proposals of Immanuel Kant (1724-1804) focusing on some of his practical philosophy such as Morality, Religion and Education. The aim into attempting to rebuild the course of Kant practical philosophy is to present the development process and the contribution of pedagogy in the process of moral formation. The objective is to present in an articulated manner, the idea of progress and improvements on human conduct along with the project on the metaphysics of moral and its ending of uniting all men of good will, in other words, in an ethical community way. First, the moral law is presented as a necessary condition for a good conduct in oneself, straying from any sensible representation in which it pretends to serve as a reference to every virtuous conduct. The explanation being held in this study is only about the possibility of a purely moral conduct, and only if the reference for the formulation of a good character is based on the rational law. However, the requisite for a good moral character is only valid if in accordance with practical reason law. Concerning the union of men, the consequence of this match is the origin of evil just as the union of some equal virtuous interest is capable of overcoming bad actions due to ideas of an ethic community. Finally, in the third chapter, the research strategy does not apply only to Pedagogy but also to other several masterworks, aiming to systematize the proposal of a moral education, seen by Kant, as essential and indispensable on the formation of a virtuous individual member of a certain ethic community.